Negative electrode mixture, method for producing negative electrode mixture, and all-solid-state battery

By coating the coated layer of borohydride solid electrolyte containing LiBH4 and LiX on the surface of the negative electrode active material of the all-solid battery, combining the sulfide solid electrolyte to form a negative electrode composite, the sulfide solid electrolyte is solved, and the resistance increases are increased due to the sulfide solid electrolyte being easily reduced. The problem is that the cycle characteristics and charging capacity maintenance rate of the battery are improved.

CN119133375APending Publication Date: 2024-12-13TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410718953.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-13
Filing Date
2024-06-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The sulfide solid electrolyte is easily reduced in all solid batteries, resulting in a deterioration layer forming on the surface of the negative electrode active material, increasing resistance, and affecting the cycle life and output power of the battery.

Method used

The coated negative electrode active material is used to coat the coated layer of borohydride solid electrolyte containing LiBH4 and LiX, and combined with the sulfide solid electrolyte, a negative electrode composite is formed to suppress the formation of the deteriorated layer and the increase in resistance.

Benefits of technology

It effectively suppresses the increase in resistance, improves the cycle characteristics and ion conductivity of the battery, extends the service life of the battery, and maintains the charging capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133375A_ABST
    Figure CN119133375A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode mixture, a method for manufacturing the negative electrode mixture, and an all-solid-state battery. The main purpose of the present invention is to provide a negative electrode mixture capable of suppressing an increase in resistance. The present disclosure solves the above-mentioned problem by providing a negative electrode mixture for an all-solid-state battery, the negative electrode mixture containing a coated negative electrode active material and a sulfide solid electrolyte, the coated negative electrode active material has a negative electrode active material and a coating layer that covers at least a portion of the surface of the negative electrode active material, the coating layer contains a borohydride solid electrolyte, the borohydride solid electrolyte contains LiBH4 and LiX, and X is selected from Cl, Br, or I.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a negative electrode composite material, a method for manufacturing the negative electrode composite material, and an all-solid-state battery. Background Art

[0002] All-solid batteries are batteries with a solid electrolyte layer between the positive electrode active material layer and the negative electrode active material layer. Compared with liquid batteries with electrolytes containing flammable organic solvents, they have the advantage of being easy to simplify safety devices. Among them, all-solid batteries using sulfide-based solid electrolytes have been actively studied in recent years due to their high ion conductivity and good formability. In addition, research on adding additives is also underway to improve the conductivity of solid electrolytes.

[0003] For example, Patent Document 1 discloses a solid electrolyte comprising a sulfide solid electrolyte and LiBH4 in which LiX is solid-dissolved, and a solid-state battery comprising the solid electrolyte. In addition, Patent Document 2 discloses a method for manufacturing a solid-state battery containing a borohydride compound as a solid electrolyte.

[0004] However, all-solid-state batteries face challenges such as improving cycle life and output power. In addition to improving the ion conductivity of the solid electrolyte, measures such as reducing the resistance of the electrode layer and inhibiting material degradation are also needed.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-134316

[0008] Patent Document 2: International Publication No. 2019 / 078130 Summary of the invention

[0009] Problems to be solved by the invention

[0010] Regarding the above, although the sulfide solid electrolyte exhibits good ion conductivity, it is easily reduced, and a deteriorated layer may be formed on the surface of the negative electrode active material in contact with the sulfide solid electrolyte, which may increase the resistance.

[0011] The present disclosure has been made in view of the above-mentioned actual situation, and a main object of the present disclosure is to provide a negative electrode composite material (negative electrode composite material) capable of suppressing an increase in electrical resistance.

[0012] Means for solving problems

[0013] [1] A negative electrode composite material for an all-solid-state battery, comprising a coated negative electrode active material and a sulfide solid electrolyte, wherein the coated negative electrode active material comprises a negative electrode active material and a coating layer that covers at least a portion of the surface of the negative electrode active material, wherein the coating layer comprises a borohydride solid electrolyte, and wherein the borohydride solid electrolyte comprises LiBH4 and LiX, wherein X is selected from Cl, Br or I.

[0014] [2] The negative electrode composite material according to [1], wherein the coated negative electrode active material contains graphite as the negative electrode active material.

[0015] [3] The negative electrode composite material according to [1] or [2], wherein, in the coated negative electrode active material, the proportion of the borohydride solid electrolyte relative to the total of the negative electrode active material and the borohydride solid electrolyte is greater than or equal to 0.8 volume % and less than or equal to 22 volume %.

[0016] [4] The negative electrode composite material according to any one of [1] to [3], wherein, in the coated negative electrode active material, the proportion of the borohydride solid electrolyte relative to the total of the negative electrode active material and the borohydride solid electrolyte is 1.5 volume % or more and 15 volume % or less.

[0017] [5] The negative electrode composite material according to any one of [1] to [4], wherein the borohydride solid electrolyte contains at least LiCl as the LiX.

[0018] [6] The negative electrode composite material according to any one of [1] to [5], wherein the sulfide solid electrolyte contains an argyrodite-type sulfide solid electrolyte.

[0019] [7] A method for manufacturing a negative electrode composite material is a method for manufacturing a negative electrode composite material according to any one of [1] to [6], comprising: a coating step for obtaining the coated negative electrode active material; and a mixing step for mixing the coated negative electrode active material and the sulfide solid electrolyte to obtain the negative electrode composite material, wherein the coating step comprises: a precursor layer forming treatment, wherein a precursor solution containing the LiBH4 and the LiX is applied to the surface of the negative electrode active material, and the negative electrode active material coated with the precursor solution is dried to form a precursor layer; and a coating layer forming treatment, wherein the precursor layer is heated to form a coating layer containing the borohydride solid electrolyte.

[0020] [8] An all-solid-state battery, comprising a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer arranged between the positive electrode active material layer and the negative electrode active material layer, wherein the negative electrode active material layer contains the negative electrode composite material according to any one of [1] to [6].

[0021] Effects of the Invention

[0022] The present disclosure has the effect of being able to provide a negative electrode composite material capable of suppressing an increase in electrical resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic cross-sectional view illustrating the coated negative electrode active material in the present disclosure.

[0024] Figure 2 This is a schematic cross-sectional view illustrating an all-solid-state battery in the present disclosure.

[0025] Figure 3 It is a graph showing the relationship between the amount of coating material and the capacity retention rate in Examples 1 to 4 and Comparative Example 1.

[0026] Description of Reference Numerals

[0027] 1…Coated negative electrode active material

[0028] 2…Negative electrode active material

[0029] 3…Coating layer

[0030] 10…All-solid-state battery

[0031] 11…Positive electrode active material layer

[0032] 12…Negative electrode active material layer

[0033] 13…Solid electrolyte layer

[0034] 14…Positive electrode collector

[0035] 15…Negative electrode collector DETAILED DESCRIPTION

[0036] The negative electrode composite material, the method for producing the negative electrode composite material, and the all-solid-state battery in the present disclosure are described in detail below.

[0037] A. Negative electrode composite material

[0038] The negative electrode composite in the present disclosure is a negative electrode composite for an all-solid-state battery, comprising a coated negative electrode active material and a sulfide solid electrolyte. In addition, the coated negative electrode active material has a negative electrode active material and a coating layer that covers at least a portion of the surface of the negative electrode active material, and the coating layer contains a borohydride solid electrolyte (borohydride-based solid electrolyte), and the borohydride solid electrolyte contains LiBH4 and LiX (X is selected from Cl, Br or I). Furthermore, in the present disclosure, the borohydride solid electrolyte in the coating layer is sometimes referred to as solid electrolyte A (SE-A), and the sulfide solid electrolyte in the negative electrode composite is referred to as solid electrolyte B (SE-B). In addition, in this specification, the so-called "surface" of the negative electrode active material includes not only the outer surface of the negative electrode active material (negative electrode active material particles), but also a portion that can be in contact with a liquid such as a precursor solution described later.

[0039] According to the present disclosure, since the coating layer covering the negative electrode active material contains a predetermined borohydride-based solid electrolyte, it is possible to provide a negative electrode composite material capable of suppressing an increase in resistance.

[0040] As mentioned above, although the sulfide solid electrolyte has good ion conductivity, it is easily reduced, and a deterioration layer may be formed on the surface of the negative electrode active material when the battery is repeatedly charged and discharged. The negative electrode composite material disclosed in the present invention contains a specified coated negative electrode active material. In the coated negative electrode active material, the negative electrode active material is coated with a coating layer containing a specified borohydride solid electrolyte with good reduction resistance. Therefore, even if the battery is repeatedly charged and discharged, the formation of the deterioration layer is suppressed, the increase in resistance can be suppressed, and the cycle characteristics of the battery can be improved. In addition, since it contains a sulfide solid electrolyte with good ion conductivity together with the above-mentioned coated negative electrode active material, it becomes a negative electrode composite that can suppress the initial resistance. Furthermore, when a deterioration layer is formed, it is possible to hinder the movement of carrier ions such as Li ions and reduce the ion conductivity, but in the negative electrode composite material disclosed in the present invention, by suppressing the formation of the deterioration layer, the advantage of being able to suppress the reduction in ion conductivity is also obtained.

[0041] 1. Coating negative electrode active material

[0042] Figure 1 This is a schematic cross-sectional view illustrating the coated negative electrode active material in the present disclosure. Figure 1 As shown, the coated negative electrode active material 1 comprises a negative electrode active material 2 and a coating layer 3 that covers at least a portion of the surface of the negative electrode active material. In addition, the coating layer 3 contains a predetermined borohydride solid electrolyte.

[0043] (1) Negative electrode active material

[0044] The negative electrode active material in the present disclosure is not particularly limited as long as it is a material that functions as a negative electrode active material in a battery. Examples of negative electrode active materials include carbon-based active materials such as natural graphite, artificial graphite, graphene, hard carbon, and soft carbon; Nb2O5, Li4Ti5O 12 and oxide active materials such as SiO; and metal active materials such as simple substance In, simple substance Al, simple substance Si, simple substance Sn and alloys of these metals. Among these, graphite is preferred. In addition, the negative electrode active material may be only one kind or two or more kinds.

[0045] The shape of the negative electrode active material is, for example, a particle shape. In addition, the negative electrode active material may be a primary particle or a secondary particle.

[0046] The average particle size of the negative electrode active material (D 50 ) is, for example, 10 nm or more, 100 nm or more, 500 nm or more, 1 μm or more, or 5 μm or more. On the other hand, the average particle size (D 50 ) is, for example, 50 μm or less, 40 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less. 50 ) refers to the cumulative 50% particle size in the volume-based particle size distribution using a laser diffraction particle size distribution measuring device. 50 ) may be the average particle size of primary particles or the average particle size of secondary particles. 50 ) refers to the cumulative 50% particle size in a volume-based particle size distribution using a laser diffraction particle size distribution measuring apparatus.

[0047] (2) Coating layer

[0048] The coating layer in the present disclosure covers at least a portion of the surface of the above-mentioned negative electrode active material and contains a borohydride solid electrolyte, and the borohydride solid electrolyte contains LiBH4 and LiX (X is selected from Cl, Br or I). In addition, regarding the "surface", as described above, the coating layer usually covers at least a portion of the outer surface of the negative electrode active material.

[0049] The borohydride solid electrolyte has, for example, a composition represented by αLiBH4-LiX (X is at least one selected from Cl, Br or I). α is, for example, a number greater than or equal to 1 and less than or equal to 5, and X is as described above. In particular, the composition of the borohydride solid electrolyte is preferably represented by 3LiBH4-LiX.

[0050] The borohydride solid electrolyte may contain only one of LiCl, LiBr and LiI as the above-mentioned LiX, or may contain two or more thereof. In particular, the borohydride solid electrolyte preferably contains LiCl as the above-mentioned LiX. For example, when the borohydride solid electrolyte contains two or more LiX, the ratio of LiCl in all LiX is preferably 50% or more.

[0051] The borohydride solid electrolyte is preferably a solid solution of the above-mentioned LiBH4 and LiX.

[0052] The coating layer may be a layer containing only the borohydride solid electrolyte as a material or a layer containing other materials. In the latter case, the proportion of the borohydride solid electrolyte in all materials constituting the coating layer is preferably 50% or more.

[0053] The coating layer may cover a part of the surface of the negative electrode active material or the entire surface. The coverage rate may be, for example, 10% or more, 30% or more, 50% or more, 70% or more, or 90% or more. On the other hand, the coverage rate may be 100% or less. In the latter case, the coverage rate may be, for example, 99% or less, 97% or less, 95% or less, or 93% or less.

[0054] The average thickness of the coating layer is, for example, 5 nm or more, 50 nm or more, or 100 nm or more. On the other hand, the average thickness of the coating layer is, for example, 1000 nm or less, 500 nm or less, or 300 nm or less.

[0055] The coverage rate and the average thickness can be determined by, for example, microscopic observation using a scanning electron microscope (SEM) or XPS (X-ray photoelectron spectroscopy).

[0056] In the coated negative electrode active material, the proportion of the borohydride solid electrolyte relative to the total of the negative electrode active material and the borohydride solid electrolyte is, for example, 0.8% by volume or more, 1.5% by volume or more, 4% by volume or more, or 7% by volume or more. On the other hand, the above proportion is, for example, 22% by volume or less, 18% by volume or less, 15% by volume or less, or 11% by volume or less. In addition, in this specification, the above proportion can also be referred to as "the amount of the coating material".

[0057] In addition, if the coating material amount is expressed on a weight basis, the coating material amount is, for example, 0.5 weight % or more, 1 weight % or more, 3 weight % or more, or 5 weight % or more. On the other hand, the coating material amount is, for example, 15 weight % or less, 12 weight % or less, 10 weight % or less, or 7 weight % or less.

[0058] Among them, the coating layer can cover the surface of the primary particles of the negative electrode active material, and can also cover the surface of the secondary particles formed by the agglomeration of the primary particles of the negative electrode active material. In addition, when the coated negative electrode active material is a secondary particle, the coating layer can cover the surface of both the primary particles and the secondary particles of the negative electrode active material. In this case, it can be understood that the above-mentioned borohydride solid electrolyte is arranged on the surface (surface of the secondary particles) and the inside (surface of the primary particles) of the coated negative electrode active material. In addition, the coating layer preferably directly covers the negative electrode active material.

[0059] (3) Coating of negative electrode active material

[0060] The shape of the coated negative electrode active material is, for example, a particle shape. In addition, the coated negative electrode active material may be a primary particle or a secondary particle. The average particle size (D 50 ) is, for example, 10 nm or more and 50 μm or less. The above average particle size may be the average particle size of primary particles or the average particle size of secondary particles. 50 ), as described above.

[0061] The proportion of the negative electrode active material coated in the negative electrode composite is, for example, 40 volume % or more, 50 volume % or more, or 70 volume % or more. On the other hand, the proportion of the negative electrode active material coated is, for example, 90 volume % or less, or 80 volume % or less.

[0062] The method for preparing the coated negative electrode active material will be described later.

[0063] 2. Sulfide solid electrolyte

[0064] The sulfide solid electrolyte in the present disclosure is generally a solid electrolyte containing sulfur (S) as a main component of an anion element.

[0065] As the sulfide solid electrolyte, for example, a solid electrolyte containing Li element, A element (A is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, In), and S element can be listed. In addition, the sulfide solid electrolyte may further contain at least one of O element and halogen element. As the halogen element, for example, F element, Cl element, Br element, I element can be listed. The sulfide solid electrolyte may be glass (amorphous), glass ceramic, or crystal.

[0066] As the sulfide solid electrolyte in the present disclosure, an argyrodite-type sulfide solid electrolyte is particularly preferred. The so-called "argyrodite-type sulfide solid electrolyte" refers to a sulfide solid electrolyte having an argyrodite-type crystal phase. Whether or not there is an argyrodite-type crystal phase can be confirmed by, for example, performing an X-ray diffraction measurement (XRD measurement). In addition, in the argyrodite-type sulfide solid electrolyte, it is preferred to have an argyrodite-type crystal phase as the main phase.

[0067] The composition of the argyrodite-type sulfide solid electrolyte is not particularly limited, and examples thereof include Li 7-y PS 6- y X' y (X' is a halogen element, and y is a number satisfying 0≤y≤2).

[0068] The sulfide solid electrolyte preferably has high ion conductivity. The ion conductivity at 25°C is, for example, 0.5×10 -3 S / cm or more, can be 1×10 -3 S / cm or more, can be 2×10 -3 S / cm or more.

[0069] The shape of the sulfide solid electrolyte may be, for example, a particle shape. The average particle size (D 50 ) is, for example, 10 nm or more and 50 μm or less. 50 ), as described above.

[0070] The proportion of the sulfide solid electrolyte in the negative electrode composite is, for example, 10% by volume or more, 30% by volume or more, or 50% by volume or more. On the other hand, the proportion of the sulfide solid electrolyte is, for example, 60% by volume or less.

[0071] 3. Negative electrode composite material

[0072] The negative electrode composite material in the present disclosure may further contain at least one of a conductive material and a binder.

[0073] As the conductive material, for example, carbon materials, metal particles, and conductive polymers can be listed. As the carbon material, for example, acetylene black (AB) and Ketjen black (KB) and other particulate carbon materials; and fibrous carbon materials such as carbon fiber, carbon nanotube (CNT) and carbon nanofiber (CNF). In addition, as the adhesive, for example, fluorine-containing adhesives such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), rubber adhesives such as butadiene rubber, and acrylic adhesives can be listed.

[0074] In addition, the negative electrode composite material may be a negative electrode slurry containing a dispersion medium. As the dispersion medium, for example, organic solvents such as butyl butyrate, dibutyl ether, heptane and tetrahydrofuran can be listed. By applying the negative electrode slurry to a substrate such as a collector and drying it, a negative electrode active material layer containing the negative electrode composite material can be formed. On the other hand, the negative electrode composite material may not contain a dispersion medium.

[0075] The negative electrode composite material in the present disclosure is generally used for the negative electrode active material layer in an all-solid-state battery. The all-solid-state battery is described in "C. All-solid-state battery".

[0076] B. Method for manufacturing negative electrode composite material

[0077] The method for producing a negative electrode composite material in the present disclosure includes a predetermined coating step and a mixing step.

[0078] 1. Coating process

[0079] The coating step in the present disclosure is a step of obtaining the above-mentioned coated negative electrode active material, and includes a predetermined precursor layer forming process and a coating layer forming process.

[0080] (1) Precursor layer formation process

[0081] The precursor layer forming process is a process of applying a precursor solution containing the above-mentioned LiBH4 and the above-mentioned LiX to the surface of the above-mentioned negative electrode active material and drying the negative electrode active material coated with the above-mentioned precursor solution to form a precursor layer.

[0082] The precursor solution can be prepared by mixing a solvent containing LiBH4 and a solvent containing LiX so that LiBH4 and LiX are in a desired ratio as described in the examples described later. Examples of the solvent include organic solvents such as tetrahydrofuran (THF).

[0083] There is no particular limitation on the coating method, and for example, a method of immersing the negative electrode active material in the precursor solution and stirring can be cited. In addition, as far as the drying conditions such as drying temperature and drying time are concerned, there is no particular limitation as long as the above-mentioned solvent can be removed from the precursor solution. For example, the drying temperature is 80° C. or more and 100° C. or less, and the drying time is, for example, 5 minutes or more and 1 hour or less.

[0084] In the coating layer forming process described later, the above-mentioned coating and drying may be repeated multiple times in order to form a coating layer having a desired thickness and coverage.

[0085] (2) Coating layer formation process

[0086] The coating layer forming process in the present disclosure is a process of heating the above-mentioned precursor layer to form the coating layer. The coating layer is the same as that described in "A. Negative electrode composite material", so the description here is omitted.

[0087] The heating temperature and heating time are not particularly limited as long as the desired coating layer can be formed. The heating temperature is, for example, 80° C. to 150° C., and the heating time is, for example, 30 minutes to 2 hours. In addition, the heating can be performed under a reduced pressure environment such as a vacuum.

[0088] (3) Coating of negative electrode active material

[0089] The contents of the coated negative electrode active material are the same as those described in "A. Negative electrode composite material", and thus the description thereof is omitted here.

[0090] 2. Mixing process

[0091] The mixing step in the present disclosure is a step of mixing the coated negative electrode active material and the sulfide solid electrolyte layer to obtain the negative electrode composite material.

[0092] The ratio of the coated negative electrode active material and the sulfide solid electrolyte is the same as that described in "A. Negative electrode composite material". In addition, in the mixing process, the coated negative electrode active material and the sulfide solid electrolyte can be mixed with at least one of the conductive material and the binder in the presence of a dispersion medium. The conductive material, the binder and the dispersion medium are the same as those described in "A. Negative electrode composite material". There is no particular limitation on the mixing method, and a conventionally known method can be used.

[0093] 3. Negative electrode composite material

[0094] The negative electrode composite material produced by the above method is the same as that described in "A. Negative electrode composite material", so the description here is omitted.

[0095] C. All-solid-state battery

[0096] Figure 2 This is a schematic cross-sectional view illustrating an all-solid-state battery in the present disclosure. Figure 2 The all-solid battery 10 shown has a positive electrode active material layer 11, a negative electrode active material layer 12, and a solid electrolyte layer 13 formed between the positive electrode active material layer 11 and the negative electrode active material layer 12, and the negative electrode active material layer 12 contains the above-mentioned negative electrode composite. In addition, the all-solid battery 10 has a positive electrode collector 14 for collecting current from the positive electrode active material layer 11, and a negative electrode collector 15 for collecting current from the negative electrode active material layer 12.

[0097] The all-solid-state battery in the present disclosure is an all-solid-state battery with a good charge capacity retention rate because the negative electrode active material layer contains the above-mentioned negative electrode composite.

[0098] 1. Negative electrode active material layer

[0099] The negative electrode active material layer contains the negative electrode mixture described above. The negative electrode mixture is the same as described in "A. Negative electrode mixture", so the description here is omitted. The thickness of the negative electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.

[0100] 2. Positive electrode active material layer

[0101] The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material layer preferably contains at least one of a solid electrolyte, a conductive material, and a binder as required. As the positive electrode active material, the conductive material, and the binder, conventionally known materials can be cited. In addition, the positive electrode active material layer preferably contains the above-mentioned sulfide solid electrolyte as a solid electrolyte. The thickness of the positive electrode active material layer is, for example, greater than 0.1 μm and less than 1000 μm.

[0102] 3. Solid active material layer

[0103] The solid electrolyte layer contains at least a solid electrolyte and may contain a binder as required. The binder is as described above. In addition, the solid electrolyte is preferably the above-mentioned sulfide solid electrolyte. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.

[0104] 4. Positive electrode collector and negative electrode collector

[0105] The material of the positive electrode current collector and the negative electrode current collector may be, for example, a conventionally known metal material such as Al, SUS, Cu, and Ni.

[0106] 5. All-solid-state batteries

[0107] The all-solid battery in the present disclosure is typically a lithium ion secondary battery. In addition, as the purpose of the all-solid battery, for example, the power supply of vehicles such as hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), electric vehicles (BEV), gasoline vehicles, and diesel vehicles can be listed. In particular, it is preferably used for the driving power supply of hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV) or electric vehicles (BEV). In addition, the all-solid battery can be used as a power supply for mobile bodies (such as railways, ships, aircraft) other than vehicles, and can also be used as a power supply for electrical products such as information processing devices.

[0108] It should be noted that the present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and technical solutions having substantially the same configuration and achieving the same effects as the technical ideas described in the patent claims of the present disclosure are all included in the technical scope of the present disclosure.

[0109] Example

[0110] [Example 1]

[0111] (Preparation of coated negative electrode active material)

[0112] A tetrahydrofuran (THF) solution containing LiBH4 and a THF solution containing LiI are mixed in such a way that the molar ratio of LiBH4 to LiI becomes 3:1. Thus, a precursor solution (THF solution containing 3LiBH4-LiI) is prepared. Next, the precursor solution is added to the negative electrode active material (spherical natural graphite, particle size 16 μm), and dried on a hot plate at 80°C, and this operation is repeated several times. Thus, adjustment is made so that the amount of coated material (SE-A / (graphite+SE-A)) becomes the value in Table 1. Then, vacuum drying is performed at 120°C for 1 hour. Thus, a coated negative electrode active material (coated graphite) is prepared.

[0113] (Manufacturing of negative electrode composite material)

[0114] Argentum-type sulfide solid electrolyte (SE-B) was added to the above-mentioned coated graphite, and they were carefully mixed in a mortar. Thus, a negative electrode composite was prepared. Furthermore, the amount of argyrodite-type sulfide solid electrolyte was adjusted so that the composition of the negative electrode composite became the value in Table 1.

[0115] (Production of Evaluation Batteries)

[0116] As an evaluation battery (negative electrode half-cell), a powder battery cell including a cylindrical non-conductive ceramic rail with an inner diameter of 11.28 mm and a stainless steel collector was prepared. Specifically, the above-mentioned negative electrode composite material was put into the ceramic rail so that the amount of graphite became 8 mg, 0.1 g of argyrodite-type sulfide-based solid electrolyte was put in, and pressed at 588 MPa to produce a negative electrode active material layer and a separator layer. Then, In-Li foil was arranged on the separator layer as a counter electrode, and then pressed at 98 MPa. Then, it was constrained with a constraining fixture. In this way, an evaluation battery was produced.

[0117] [Example 2 to Example 4]

[0118] An evaluation battery was produced in the same manner as in Example 1 except that the coated negative electrode active material and the negative electrode composite were produced so that the amount of the coating material and the composition of the negative electrode composite material were the values ​​shown in Table 1.

[0119] [Comparative Example 1]

[0120] In the preparation of the coated negative electrode active material, the coated negative electrode active material was prepared in the same manner as in Example 1, except that the above-mentioned argyrodite-type sulfide solid electrolyte was used instead of the borohydride solid electrolyte (3LiBH4-LiI). Using the coated negative electrode active material, a negative electrode composite was prepared in a manner such that the composition became the value in Table 1, and an evaluation battery was prepared in the same manner as in Example 1, except that.

[0121] [Comparative Example 2]

[0122] Spherical natural graphite was used instead of the coated negative electrode active material. In addition, graphite, 3LiBH4-LiI, and argyrodite-type sulfide solid electrolyte were carefully mixed together in a mortar so that the composition of the negative electrode composite material was in the proportion shown in Table 1, thereby preparing a negative electrode composite material. That is, no coated graphite was prepared. Except for using the above-mentioned negative electrode composite material, an evaluation battery was prepared in the same manner as in Example 1.

[0123] [evaluate]

[0124] (Impedance measurement and capacity retention rate measurement)

[0125] The evaluation batteries of Examples 1 to 4 and Comparative Examples 1 to 2 were evaluated for cell resistance and charge capacity retention as follows. The results are shown in Tables 2 and Figure 3 .

[0126] First, set the 1C current to 2.72 mA / cm 2 , at 0.1C-CCCV, 1.5-0.05V(vsLi + / Li) and 25°C, and three cycles of charge and discharge (final charge and discharge) were performed.

[0127] Then, the battery was charged to 1.1 mAh, and impedance measurement was performed under the conditions of a voltage width of 10 mV, a frequency range of 7 MHz to 0.01 Hz, and 25° C. to measure the initial resistance.

[0128] Secondly, at 60℃, 1.5-0.05V(vsLi + The resistance increase rate was calculated from the resistance after 20 cycles and the initial resistance.

[0129] For each evaluation battery whose resistance increase rate was calculated, +The charge rate test was conducted under the conditions of 0.1, 0.2, 0.3, and 0.5 C CC charging and 0.1 C CCCV discharge. The charge capacity retention rate at 0.5 C was calculated based on the 0.1 C charge capacity.

[0130]

Table 1

[0131]

[0132]

Table 2

[0133]

[0134] As shown in Table 2, all the examples significantly suppressed the resistance increase rate compared with Comparative Examples 1 and 2, and the capacity retention rate was also good. Figure 3 The results of Examples 1 to 4 shown in (a) and (b) confirmed that a better capacity retention rate can be obtained by adjusting the amount of the coating material (weight % and volume %).

[0135] [Examples 5 and 6]

[0136] Using the coating material (solid electrolyte of borohydride: SE-A) shown in Table 3, a coated negative electrode active material was prepared in such a manner that the amount of the coating material became the value shown in Table 3. In the same manner as in Example 1, except that the coated negative electrode active material was used, a negative electrode composite and an evaluation battery were prepared, and the above-mentioned evaluation was performed. The results are shown in Table 3. In Example 6, the resistance increase rate was a negative value, but for convenience, the resistance increase rate was recorded as 0%.

[0137]

Table 3

[0138]

[0139] It can be seen from Examples 1, 5 and 6 that when 3LiBH4-LiCl is used as the coating material, the resistance increase rate is most suppressed and the capacity retention rate is also good.

[0140] [Comparative Examples 3 to 5]

[0141] Graphite that was not coated and the borohydride solid electrolyte (SE-A) shown in Table 4 were mixed in a mortar at the ratio shown in Table 4 to prepare a negative electrode composite. An evaluation battery was prepared in the same manner as in Example 1 except that the negative electrode composite was used. The initial resistance of the prepared evaluation battery was measured by the above-mentioned method. The results are shown in Table 4.

[0142]

Table 4

[0143]

[0144] From Comparative Example 2 and Comparative Examples 3 to 5, it was confirmed that the initial resistance can be suppressed by using a sulfide solid electrolyte in the negative electrode composite material.

[0145] From the above results, it was confirmed that by using the negative electrode composite material disclosed in the present invention, an increase in resistance can be suppressed, and an all-solid-state battery with a good capacity retention rate can be obtained.

Claims

1. A negative electrode composite material for an all-solid-state battery, comprising a coated negative electrode active material and a sulfide solid electrolyte, wherein the coated negative electrode active material comprises a negative electrode active material and a coating layer that covers at least a portion of the surface of the negative electrode active material, wherein the coating layer comprises a borohydride solid electrolyte, and the borohydride solid electrolyte comprises LiBH4 and LiX, wherein X is selected from Cl, Br or I.

2. The negative electrode composite material according to claim 1, wherein The coated negative electrode active material contains graphite as the negative electrode active material.

3. The negative electrode composite material according to claim 1, wherein In the coated negative electrode active material, a ratio of the borohydride solid electrolyte to the total of the negative electrode active material and the borohydride solid electrolyte is 0.8 volume % or more and 22 volume % or less.

4. The negative electrode composite material according to claim 1, wherein In the coated negative electrode active material, a ratio of the borohydride solid electrolyte to the total of the negative electrode active material and the borohydride solid electrolyte is 1.5 volume % or more and 15 volume % or less.

5. The negative electrode composite material according to claim 1, wherein The borohydride solid electrolyte contains LiCl as the LiX.

6. The negative electrode composite material according to claim 1, wherein: The sulfide solid electrolyte includes an argyrodite-type sulfide solid electrolyte.

7. A method for producing a negative electrode composite material, the method for producing a negative electrode composite material according to any one of claims 1 to 6, comprising: A coating step of obtaining the coated negative electrode active material; and a mixing step of mixing the coated negative electrode active material and the sulfide solid electrolyte to obtain the negative electrode composite material, The coating process comprises: A precursor layer forming process, wherein Applying a precursor solution containing the LiBH4 and the LiX on the surface of the negative electrode active material, and drying the negative electrode active material coated with the precursor solution to form a precursor layer; and The coating layer forming process includes heating the precursor layer to form a coating layer containing the borohydride solid electrolyte.

8. An all-solid-state battery, comprising a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer arranged between the positive electrode active material layer and the negative electrode active material layer, wherein the negative electrode active material layer contains the negative electrode composite material described in any one of claims 1 to claim 6.

Citation Information

Patent Citations

  • Solid electrolyte

    JP2016134316A

  • Production method for all-solid-state battery

    WO2019078130A1